Anxiety, Depression, and Stress Reaction/Adjustment Disorders and Their Associations with Healthcare Resource Utilization and Costs Among Newly Diagnosed Patients With Breast Cancer - Dingwei Dai; Henriette Coetzer; Sean R. Zion; Michael J. Malecki (Journal of Health Economics and Outcomes Research)
**Background:** Breast cancer is the most common cancer among women in the United States. Newly diagnosed patients with breast cancer often experience anxiety, depression, and stress. However, the impact of psychological distress on healthcare resource utilization (HCRU) and costs has not been adequately assessed.